Plasminogen activator inhibitor-1 serum levels in frontotemporal lobar degeneration - Angelucci, Francesco; Veverova, Katerina; Katonová, Alžbeta; Vyhnalek, Martin; Hort, Jakub (Journal of cellular and molecular medicine, 2024)
Plasminogen activator inhibitor-1 (PAI-1) impedes brain plasmin synthesis. Reduced plasmin activity facilitates cumulation of amyloid beta (Aβ) in Alzheimer's disease (AD). Since plasmin also regulates the synaptic activity, it is possible that altered PAI-1 is present in other neurodegenerative disorders. We investigated whether PAI-1 and its counter-regulatory tissue plasminogen activator (tPA) are altered in serum of patients with dementia due to frontotemporal lobar degeneration (FTLD). Thirty five FTLD patients (21 in mild cognitive impairment stage (MCI) and 14 in dementia stage) and 10 cognitively healthy controls were recruited. Serum tPA and PAI-1 protein levels were measured by anova. Correlation between biochemical and demographic data were explored by measuring Pearson correlation coefficient. Serum PAI-1 levels were elevated in the FTLD dementia group as compared to FTLD MCI and controls. tPA serum levels and PAI-1/tPA ratio did not significantly differ among groups. There was a negative correlation between PAI-1 serum levels and disease severity measured by MMSE score. No correlations of tPA serum levels and PAI-1/tPA ratio with MMSE were found. Increased PAI-1 serum levels may serve as a marker of dementia in FTLD, suggesting that, besides Aβ pathway, the plasmin system may affect cognition through synaptic activity.
Keywords: Humans; Case-Control Studies; lidé středního věku; studie případů a kontrol; Female; Aged; senioři; lidé; Biomarkers; Tissue Plasminogen Activator; ženské pohlaví; biologické markery; Male; tkáňový aktivátor plazminogenu; Middle Aged; Cognitive Dysfunction; frontotemporální lobární degenerace; Frontotemporal Lobar Degeneration; inhibitor aktivátoru plazminogenu 1; mužské pohlaví; Plasminogen Activator Inhibitor 1; kognitivní dysfunkce